Peran Peran Sistem Informasi Manajemen dalam Meningkatkan Kualitas Pelayanan Pendidikan di Era Digital - Muhammad Ibnu Faruk Fauzi; Siti Maryam (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This study aims to thoroughly examine the role of Management Information Systems (MIS) in enhancing the quality of educational services in the ever-evolving digital era. The problem formulation addressed in this research is how MIS can significantly contribute to the efficiency and effectiveness of educational services. The methodology employed in this study is a qualitative approach with case studies from various educational institutions, including elementary schools and universities. The findings reveal that the implementation of MIS significantly enhances information accessibility for students, parents, and teachers, accelerates administrative processes, and improves communication among all educational stakeholders. Furthermore, the use of MIS facilitates accurate and timely data-driven decision-making. The discussion in this research emphasizes the importance of user training and technological support to maximize the potential of MIS and reduce resistance to change. The conclusion of this study asserts that MIS plays a crucial role in achieving high-quality educational services that are responsive to the needs of students in the digital era.